3563 Clinical research training methods that improve self-efficacy in clinical research domains. (27th March 2019) - Sebastian, Mathew; Robinson, Matthew; Dumeny, Leanne; Dyson, Kyle; McCormack, Wayne T.; May, William Stratford
Abstract : OBJECTIVES/SPECIFIC AIMS: The study aims to determine the current clinical research training interventions of MD-PhD programs and how effective they are in promoting clinical research self-efficacy. METHODS/STUDY POPULATION: A national survey of MD-PhD trainees was conducted in 2018 to identify clinical research training methods and self-efficacy for clinical research skills. MD-PhD program directors and coordinators from 108 institutions were asked to distribute the survey to their students. Responses were received from 61 institutions (56.5%). Responses were obtained from 647 MD-PhD students in all years of training, representing 17.9% of the 3613 possible participants at the 61 medical schools represented. No compensation was provided for this study. RESULTS/ANTICIPATED RESULTS: The primary methods of clinical research training reported by students included didactics, mentored clinical research, didactics plus mentored clinical research, didactics plus clinical research practicum, and didactics plus mentored clinical research plus clinical research practicum. A quarter of all participants reported having no clinical research training. Clinical research self-efficacy was then correlated with the amount of clinical research training. Students exposed to no clinical research had the lowest self-efficacy in clinical research skills and students experiencing didactics plus mentored clinical research plus clinical research practicum had the highest perceived self-efficacy in clinical research domains. DISCUSSION/SIGNIFICANCE OF IMPACT: This is one of the first studies assessing clinical research training methods for MD-PhD students and assessing their efficacy. We found that of all students questioned, 25% mentioned had not received any type of clinical research training. The remaining students identified 5 research training methods that institutions currently use. This work highlights the importance of clinical research experience students need to improve their self-efficacy, a major influence on research career outcomes.